Field Measurement and Numerical Modelling Study on Mining-Induced Subsidence in a Typical Underground Mining Area of Northwestern China - Kai Zhang; Lu Bai; Pengfei Wang; Zhuang Zhu (Advances in Civil Engineering)
Mining-induced subsidence is a great concern for environmental protection in underground mining areas in China and all over the world. In view of the fact that the research on land degradation above underground coal mines are completely or partially independent of coal mining activity and the fact that the mechanism behind mining-induced subsidence has not been well understood, this study presents a field measurement and numerical study of mining-induced subsidence with respect to mining activity of three adjacent longwall panels in a coal mine in Northwest China. This study shows that surface subsidence lags far behind panel extraction or mining activity. The profiles of ground surface are dominated and manifested by the subsurface strata structures. The subsidence influence throughout the whole length of a longwall panel varies. Stability of strata structures within overburden before the final subsidence controls the stability of ground surface land. Chain pillars of 20 m between panels of 240 m wide with cover depth of 600 m have been crushed in the gob and do not have any function in supporting the overburden strata. The final subsidence of the three adjacent panels is far to come in the future and the land reuse above underground coal mines should be carefully planned by making sure that the gob is completely compacted or no potential secondary subsidence occurs in the future.